Microwave-treated, ultra-rapidly quenched lithium-rich lithium manganese nickel oxide and method for producing same
The development of a cobalt-free lithium-rich lithium nickel manganese oxide cathode material through microwave pyrolysis and ultra-rapid quenching addresses the cost and volatility issues of cobalt-containing materials, achieving high capacity and stability in lithium ion batteries.
Patent Information
- Application Number
- JP2024540607
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-01-03
- Publication Date
- 2025-01-24
AI Technical Summary
Cobalt-containing cathode materials in lithium ion batteries are costly and volatile due to complex supply chains, necessitating the development of reliable, cobalt-free lithium ion battery cathode materials.
A method involving the sintering of a lithium-rich metal oxide material, followed by rapid cooling to form a chemical formula Li x (Mn y Ni 1-y) 2-x O 2, utilizing microwave radiation for pyrolysis and ultra-rapid quenching to achieve a stable, cobalt-free cathode material with a layered hexagonal and monoclinic phase.
The method produces a cathode material with high specific capacity, minimal voltage loss, and reduced capacity fade, suitable for lithium ion batteries, with improved structural stability and electrochemical performance.
Smart Images

Figure 2025502008000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application is a continuation-in-part of U.S. Patent Application No. 17 / 810,722, filed July 5, 2022, and claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 296,243, filed January 4, 2022, and U.S. Provisional Patent Application No. 63 / 296,244, filed January 4, 2022, which are incorporated by reference in their entireties herein.
[0002] Technical Field The present invention relates to cathode materials for lithium ion batteries, and more particularly to lithium-rich lithium nickel manganese oxide cathode active materials and methods for making the same. [Background technology]
[0003] Cobalt-containing cathode materials in lithium-ion batteries represent a substantial portion of the cost of modern battery cells, and cobalt has a significant impact on cost. Cobalt has a complex supply chain and is therefore a volatile mineral. Thus, there is a need for reliable cobalt-free lithium-ion battery cathode materials. Summary of the Invention
[0004] According to various embodiments, a method includes sintering a lithium-rich metal oxide (LRMO) material at a sintering temperature to form a sintered LRMO material, and quenching the sintered LRMO material from the sintering temperature to room temperature in less than 500 milliseconds to form a sintered LRMO material having the chemical formula Li x (M y Ni 1-y ) 2-x and forming a quenched LRMO material represented by the formula: O2, where x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1.
[0005] According to various embodiments, a method includes pyrolyzing a precursor material using microwave radiation to form a pyrolyzed lithium-rich metal oxide (LRMO) material; sintering the thermally branched LRMO material to form a sintered LRMO material; and quenching the sintered LRMO material to form a sintered LRMO material having the chemical formula: Li x (M y Ni 1-y ) 2-x and forming a quenched LRMO material represented by the formula: O2, where x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1.
[0006] According to various embodiments, the cathode electrode active material (or active material) has the chemical formula: Li x (M y Ni 1-y ) 2-x O2 (wherein x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1). The active material includes a layered hexagonal phase and a monoclinic phase. The active material has the following: a (006)+(102):(101) X-ray diffraction peak intensity ratio of greater than 0.32; When included in a lithium-ion battery, providing a specific capacity of at least 165 mAh / g at first discharge at a C / 20 rate; When contained in a lithium-ion battery, less than a 10% loss in average discharge voltage after 100 charge / discharge cycles at a C / 20 rate; and / or Less than 10% capacity fade over 100 C / 5 charge / discharge cycles when contained in a Li-ion battery At least one of the following is shown.
[0007] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate exemplary embodiments of the invention and, together with the general description above and the detailed description below, serve to explain features of the invention. [Brief description of the drawings]
[0008] [Figure 1]FIG. 1 is a photograph of a rapid quenching system according to various embodiments of the present disclosure. [Diagram 2] FIG. 2 includes four sequential time-lapse video capture images taken at 30 frames per second illustrating the rapid quenching process according to various embodiments of the present disclosure. [Diagram 3] FIG. 3 is a graph of an X-ray diffraction (XRD) pattern for a Li(MnNi)O (wherein x=1.2 and y=0.75) material prior to rapid quenching in accordance with various embodiments of the present disclosure. [Figure 4] FIG. 4 is a graph showing an X-ray diffraction (XRD) pattern for a Li(MnNi)O (wherein x=1.2 and y=0.75) material after rapid quenching in accordance with various embodiments of the present disclosure. [Diagram 5] FIG. 5 is a graph showing the X-ray diffraction pattern for Li(MnNi)O (wherein x=1.16 and y=0.7) material processed using only microwave heating of the sol-gel precursor material for 5 minutes, according to various embodiments of the present disclosure. [Figure 6] FIG. 6 is a graph showing the X-ray diffraction pattern for Li(MnNi)O (wherein x=1.16 and y=0.7) material processed using microwave heating and ultra-rapid quenching in accordance with various embodiments of the present disclosure. [Figure 7A] FIG. 7A is a tunneling electron microscope (TEM) atomic map micrograph of a prior art LRMO material that was not subjected to rapid quenching prior to electrochemical cycling of the material. [Figure 7B] FIG. 7B is a TEM HAADF atomic map micrograph of the resulting LRMO material subjected to rapid quenching prior to electrochemical cycling of the material, according to various embodiments of the present disclosure. [Figure 8A] FIG. 8A is a graph of specific capacity versus cell potential for a comparative example of LRMO material (Lix(MnyNi1-y)2-xO2, where x=1.16 and y=0.7) that was not microwave treated or rapidly quenched (in this case, cooled relatively slowly onto a metal plate). [Figure 8B] FIG. 8B is a graph of specific capacity versus cycles for a comparative example of a LRMO material (Lix(MnyNi1-y)2-xO2, where x=1.16 and y=0.7) that was not microwave treated or rapidly quenched (in this case, cooled relatively slowly onto a metal plate). [Figure 9A] FIG. 9A is a graph showing cell potential versus specific capacity during the break-in cycle. [Figure 9B] FIG. 9B is a graph showing specific capacity versus cell potential over time. [Figure 9C] FIG. 9C is a graph showing specific capacity versus cycles at C / 20 rate. [Figure 9D] FIG. 9D is a graph showing the discharge specific capacity at a C / 5 rate with a C / 20 reference cycle for an exemplary cell including a LRMO active material according to some embodiments of the disclosure. [Figure 10A] FIG. 10A is a graph showing specific capacity versus cell potential for comparative cells containing Li(MnyNi1-y)2-xO2 (where x=1.16 and y=0.7) active material that was not microwave treated or rapidly quenched. [Figure 10B] FIG. 10B is a graph showing specific capacity versus cycle for the cell of FIG. 10A. [Figure 10C] FIG. 10C is a graph showing specific capacity versus cell potential for example cells including water-quenched Li(MnNi)O (where x=1.16 and y=0.7) active material that was not ultra-rapidly quenched. [Figure 10D] FIG. 10D is a graph showing specific capacity versus cycle number for the cell of FIG. 10C. [Figure 11A] FIG. 11A is a graph showing specific capacity versus cell potential for example cells including microwave decomposed and rapidly quenched Li(MnyNi1-y)2-xO2 (where x=1.16 and y=0.7) active material in accordance with various embodiments of the present disclosure. [Figure 11B] FIG. 11B is a graph showing specific discharge capacity versus cycle at C / 20 and C / 2 rates for the example cell of FIG. 11A. [Figure 12A] FIG. 12A is a graph showing the specific discharge capacity of a lithium-rich nickel manganese oxide material sample having the formula Li[NixLi(1 / 3-2x / 3)Mn(2 / 3-x / 3)]O2, where the nickel content x=0.25, over a series of cycling. [Figure 12B] FIG. 12B shows the full charge and discharge curves of a coin cell containing the 25Hq sample. [Figure 12C] FIG. 12C shows the full charge and discharge curves of a coin cell containing a 25 Lq sample. [Figure 12D] FIG. 12D shows the full charge and discharge curves of a coin cell containing the 25Mq sample. [Figure 13A] FIG. 13A is a graph showing the specific discharge capacity of the x=0.17 sample over a range of cycling. [Figure 13B] FIG. 13B shows the full charge and discharge curves of a coin cell containing the 17Hq sample. [Figure 13C] FIG. 13C shows the full charge and discharge curves of a coin cell containing the 17 Lq sample. [Figure 13D] FIG. 13D shows the full charge and discharge curves of a coin cell containing the 17Mq sample. [Figure 14A] FIG. 14A is a graph showing the specific discharge capacity of the x=0.10 sample over a range of cycling. [Figure 14B] FIG. 14B shows the full charge and discharge curves of a coin cell containing the 10Hq sample. [Figure 14C] FIG. 14C shows the full charge and discharge curves of a coin cell containing a 10 Lq sample. [Figure 14D] FIG. 14D shows the full charge and discharge curves of a coin cell containing a 10 Mq sample. [Figure 15A] FIG. 15A is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 25Hq sample. [Figure 15B]FIG. 15B is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 25 Lq sample. [Figure 15C] FIG. 15C is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 25Mq sample. [Figure 15D] FIG. 15D is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 17Hq sample. [Figure 15E] FIG. 15E is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 17Lq sample. [Figure 15F] FIG. 15F is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 17Mq sample. [Figure 15G] FIG. 15G is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 10Hq sample. [Figure 15H] FIG. 15H is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 10 Lq sample. [Figure 15I] FIG. 15I is a graph showing normalized and offset XRD patterns of LLRNMO powder before and after cycling for the 10 Mq sample. [Figure 16] FIG. 16 contains SEM micrographs at 50,000x of cathodes spray coated with 25Hq, 25Lq and 25Mq samples before and after cycling. [Figure 17] FIG. 17 contains SEM micrographs at 50,000x magnification of cathodes spray coated with 17Hq, 17Lq and 17Mq samples before and after cycling. [Figure 18]FIG. 18 contains SEM micrographs at 50,000x of cathodes spray coated with 10Hq, 10Lq, and 10Mq before and after cycling. [Figure 19A] FIG. 19A is a graph showing a smoothed spline fit of dQ / dV versus V for the first charge cycle of the x=0.25 sample. [Figure 19B] FIG. 19B is a graph showing a smoothed spline fit of dQ / dV versus V for the first charge cycle of the x=0.17 sample. [Figure 19C] FIG. 19C is a graph showing a smoothed spline fit of dQ / dV versus V for the first charge cycle of the x=0.10 sample. [Figure 20A] FIG. 20A is a graph showing a smoothed spline fit of dQ / dV versus V for the second charge cycle of the x=0.25 sample. [Figure 20B] FIG. 20B is a graph showing a smoothed spline fit of dQ / dV versus V for the second charging cycle of the x=0.17 sample. [Figure 20C] FIG. 20C is a graph showing a smoothed spline fit of dQ / dV versus V for the second charging cycle of the x=0.10 sample. [Figure 21A] FIG. 21A is a graph showing the first and last C / 2 discharges of the 25Hq sample. [Figure 21B] FIG. 21B is a graph showing the first and last C / 2 discharges of a 25 Lq sample. [Figure 21C] FIG. 21C is a graph showing the first and last C / 2 discharges of the 25Mq sample. [Figure 21D] FIG. 21D is a graph showing the average discharge voltage per cycle over a series of cycling for the 25Hq, 25Lq, and 25Mq samples. [Figure 22A] FIG. 22A is a graph showing the first and last C / 2 discharges of the 17Hq sample. [Figure 22B] FIG. 22B is a graph showing the first and last C / 2 discharges of a 17Lq sample. [Figure 22C] FIG. 22C is a graph showing the first and last C / 2 discharges of the 17Mq sample. [Figure 22D] FIG. 22D is a graph showing the average discharge voltage per cycle over a series of cycling for the 17Hq, 17Lq, and 17Mq samples. [Figure 23A] FIG. 23A is a graph showing the first and last C / 2 discharges of the 10Hq sample. [Figure 23B] FIG. 23B is a graph showing the first and last C / 2 discharges of a 10 Lq sample. [Figure 23C] FIG. 23C is a graph showing the first and last C / 2 discharges of the 10 Mq sample. [Figure 23D] FIG. 23D is a graph showing the average discharge voltage per cycle over a series of cycling for the 10Hq, 10Lq, and 10Mq samples. [Figure 24] FIG. 1 is a schematic diagram showing how the inclusion of phase impurities in a 25Mq sample with R-3m structure and lattice parameter a′>a leads to secondary peaks such as those seen to the left of the (104) peak of 25Mq. [Figure 25A] FIG. 25A is an SEM micrograph of the aggregates. [Figure 25B] FIG. 25B is an SEM micrograph of the aggregates. [Figure 25C] FIG. 25C is a higher magnification SEM micrograph of crystallites (eg, crystallite grains) in the aggregates. [Figure 25D] FIG. 25D is a higher magnification SEM micrograph of crystallites (eg, crystallite grains) in the aggregates. [Figure 26A]FIG. 26A is a graph of intensity (arbitrary units) versus angle 2θ (degrees) showing indexed normalized and offset XRD patterns of pristine layered lithium rich nickel manganese oxide (LLRNMO) powder. [Figure 26B] FIG. 26B includes an upper plot showing the trend between lattice parameter "a" and nickel content of the samples, and a lower plot showing the trend between lattice parameter "c" and nickel content of the samples, obtained by single-phase Rietveld fitting. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] As mentioned herein, various aspects of the disclosure will be described with reference to exemplary embodiments and / or the accompanying drawings in which exemplary embodiments of the invention are shown. However, the present invention may be embodied in many different forms and should not be construed as being limited to the exemplary embodiments shown in the drawings or described herein. It will be understood that the various disclosed embodiments may involve specific features, elements, or steps that are described in connection with a particular embodiment. It will also be understood that a specific feature, element, or step may be described in connection with a particular embodiment, but may be interchangeable or combined with another embodiment in various combinations or permutations not shown.
[0010] Various aspects will now be described in detail with reference to the accompanying drawings. Wherever possible, the same reference numbers will be used throughout the drawings to refer to the same or like parts (or components). References made to specific examples and implementations are made for illustrative purposes and are not intended to limit the scope of the invention or the claims.
[0011] Ranges may be expressed herein as from "about" one particular value and / or to "about" another particular value. When such a range is expressed, examples include from the one particular value and / or to the other particular value. Similarly, when values are expressed as approximations, using the antecedent "about" or "substantially," it is understood that the particular value forms another subject matter. In some examples, a value "about X" may include ±1% of the value of X. It is further understood that each endpoint of the range is significant both in relation to the other endpoint, and independently of the other endpoint.
[0012] According to various embodiments, a rapid and inexpensive method for forming crystallographically stable, highly durable, cobalt-free (or cobalt-free) lithium-rich metal oxide (LRMO) material is provided. In some embodiments, the LRMO material can be a lithium-rich (or lithium-rich) lithium manganese nickel oxide material represented by the following general formula 1: Li x (M y Ni 1-y ) 2-x O2 (formula 1) (wherein x is greater than 1.0 and less than 1.25, and y is in the range of 0.95 to 0.1, for example, about 0.8 to 0.5).
[0013] In some embodiments, the LRMO material can be a lithium-rich lithium manganese nickel oxide material represented by Formula 2 below: Li[Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) Ni x ]O2 (formula 2) (wherein x is in the range of 0.1 to 0.4)
[0014] LRMO materials in their pristine state (e.g., before they are charged for the first time) can have different hexagonal (e.g., rhombohedral) and monoclinic phases. Thus, LRMO materials have the formula: (1-x)[Li2MnO3]*x[LiMn a Ni(1-a) O2], where the first part of the formula refers to the relative molar amount of monoclinic phase (1-x) and the second part of the formula refers to the relative molar amount of rhombohedral phase (x). The mole fraction of the rhombohedral phase, "x", typically ranges between 0.8-0.95 and "a" ranges from 0.6-0.9. In some embodiments, the two phases may be arranged in a layered structure.
[0015] Various embodiments provide LRMO materials that exhibit high specific capacity (eg, >240 mAh / g) and a wide functional potential window (eg, 2.0-4.8 V) when used as the active material in cobalt-free cathodes.
[0016] According to various embodiments, methods for forming LRMO materials include rapid thermal processing and rapid (e.g., less than 10 seconds) or ultra-rapid (e.g., less than 500 milliseconds) quenching, which results in LRMO materials with excellent crystal structures with desired atomic order / disorder. These characteristics can provide unexpected, robust long-term stability and performance when used as cathode active materials.
[0017] Conventional LRMO materials are generally unsuitable for use as cathode active materials due to low rate performance and poor capacity retention, believed to be due to structural instability resulting from oxygen deficiency, transition metal ion migration during use, and possible manganese dissolution. The two most common aging mechanisms are manifested as a fade in average discharge voltage as the material slowly reorganizes into a dominant spinel structure, and a loss in capacity with cycling due to mechanical and / or chemical decomposition of the material.
[0018] Pyrolysis and Processing LRMO materials can be synthesized from precursor materials by a variety of methods. Table 1 below includes specific methods that can be used to synthesize LRMO, including precursor synthesis, precursor materials, quenching methods, performance metrics, and discharge capacity (DC) of LRMO material cathodes.
[0019] [Table 1]
[0020] As shown in Table 1, the three main synthetic routes for LRMO materials include precipitation followed by combustion, hydrothermal synthesis, and sol-gel solution formation followed by rapid thermal decomposition and high-temperature heat treatment (e.g., calcination, annealing, sintering).
[0021] As can be seen from Table 1, the number of studies investigating the effect of nickel composition on LRMO cathode performance has decreased over time, with studies focusing on complex nickel compositions or the formula Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) Only a few studies have investigated nickel compositions below x=0.2 with ]O2. Table 1 also shows that there are notable inconsistencies in the synthesis routes used across studies. In addition, few studies provide a detailed comparative evaluation of the impact of synthesis techniques on the performance of LRMO cathodes. In LRMO materials, transition metal order and disorder can be important, and both composition and synthesis technique can provide mechanisms to affect the degree of structural order and disorder. These structural and synthetic modifications can affect the electrochemical behavior, e.g., different defect concentrations can have pronounced effects on the performance of LRMO cathodes.
[0022] Without wishing to be bound by any particular theory, it is believed that when the sample is quenched with liquid nitrogen, the particles are immediately shielded with an insulating envelope of nitrogen gas (similar to the Leidenfrost effect), which significantly reduces thermal conductivity. In the prior art, it is believed that lithium-containing cathode materials for lithium-ion batteries cannot come into contact with moisture because water would leach out of such cathode materials and form lithium hydroxide that coats the materials. Furthermore, water is known to cause failure in lithium-ion batteries, such as lithium-ion batteries containing lithium-ion phosphate cathode materials.
[0023] Without wishing to be bound by any particular theory, the inventors believe that the relatively slow conventional quenching and cooling processes result in metal oxide agglomeration, which results in the formation of segregated nickel oxide and lithium manganese oxide phases. In particular, the nickel oxide phases may be concentrated at the surfaces of the LRMO material particles (e.g., crystallites). It is believed that this surface nickel oxide agglomeration is at least partially responsible for the chemical instability of conventional LRMO active materials.
[0024] In contrast, the inventors have unexpectedly found that water quenching does not negatively affect LRMO cathodes and does not result in leaching of lithium from such LRMO cathodes. Water quenching results in vaporization in the form of bubble nucleation and dissipation, which actually increases thermal conductivity. Thus, it is believed that water quenching has a thermal conductivity that can be roughly two orders of magnitude greater than liquid nitrogen quenching. Furthermore, both water and solvated additives therein (i.e., other materials that can dissolve in water) can react with the high temperature LRMO upon quenching to form advantageous surface terminations and / or coatings that enhance electrochemical stability and durability when used in lithium ion batteries.
[0025] Additionally, in many of the prior art quenching routes mentioned above, quenching is done on press-sintered or partially sintered pellets of intact material as larger bodies (having widths on the order of centimeters). In contrast, in embodiments of the present disclosure, quenching is done on loose and / or crushed powders of particles in the form of aggregates with an average diameter of less than 20 μm, e.g., 0.1-20 μm, e.g., 0.1-1 μm or 1-20 μm, such that when the particles are contacted with the quenching liquid (e.g., water), all of the material is cooled rapidly and at approximately the same rate. Each aggregate is composed of crystallites with an average dimension ranging from about 25 nm to about 500 nm, e.g., 50 nm to 200 nm. Each crystallite may comprise a single crystal of the LRMO material. The crystallites may be partially melted and integrated in the aggregate or completely melted and integrated in the aggregate. If the crystallites are completely fused within the agglomerates (i.e., powder particles), each crystallite comprises a single crystal grain of the powder particle, which is separated from other single crystal grains within the same powder particle by grain boundaries. The average crystal grain size of the powder particle may range from about 25 nm to about 500 nm, for example, from 50 nm to 200 nm. The agglomerates may be relatively porous, which allows water to reach the crystallites within the interior of the agglomerates.
[0026] Rapid and ultra-rapid quenching According to various embodiments, the LRMO cathode active material may be formed by heat treating (e.g., sintering, calcinating, and / or annealing) and quenching the LRMO material powder. In particular, the heat treatment may include a high temperature process in which the LRMO material may be heated to a processing temperature in the range of about 800° C. to about 1000° C., such as about 850° C. to 950° C. or 900° C. The heat treatment may be carried out in any suitable heat treatment device, such as a furnace, such as a tube furnace, a muffle box furnace, or the like. In some embodiments, the heat treatment may optionally include one or more low temperature precursor decomposition (e.g., firing) processes in which the LRMO material is heated to a temperature above room temperature and below 800° C. For example, the firing may include heating the LRMO material to a temperature in the range of about 450° C. to about 550° C., such as about 500° C., prior to the high temperature process.
[0027] According to various embodiments, the quenching process can include transferring the heated LRMO material to a quenching bath (or bath). For example, the LRMO material can be dropped directly from the thermal processing device into the quenching bath.
[0028] In conventional methods, the LRMO material may be cooled slowly during transfer from the furnace. For example, the transfer process may take about 10 seconds, during which the temperature of the LRMO material may slowly decrease. The inventors have found that slow (or sluggish) cooling prior to entry into the quench bath may result in undesirable changes to the crystal structure of the sintered LRMO material. In other words, the temperature of the sintered LRMO material upon entry into the quench bath may be important to provide the desired crystal structure. For example, slow cooling may result in a less desirable crystal structure.
[0029] According to various embodiments, the transfer process can be configured such that after a sintering process at a temperature of at least 800°C, e.g., in the range of 800°C to 950°C or about 850°C to about 925°C or about 900°C, the sintered material enters a quenching bath. For example, the transfer time from the heat treatment device to the quenching bath can be limited to 10 seconds or less, e.g., 1 second or less, e.g., less than 0.5 seconds or 0.2 seconds or less. Thus, the sintered LRMO material is cooled from a heat treatment temperature (e.g., a sintering temperature of at least 800°C, e.g., in the range of 800°C to 950°C or about 850°C to about 925°C or about 900°C) to room temperature (e.g., 25°C) in 10 seconds or less, e.g., less than 0.5 seconds, including 0.2 seconds or less. As used herein, an "ultra-rapid quenching process" may have a cooling time of less than 0.5 seconds, such as less than 0.2 seconds, for example, 0.1 to 0.2 seconds, and a "rapid quenching process" may have a cooling time of 10 seconds or less, for example, 0.5 to 10 seconds.
[0030] The sintered LRMO powder particles may be quenched in the quench bath at an average rate of at least 50° C. / s, e.g., 50° C. / s to 10,000° C. / s. For example, the sintered LRMO powder particles may be cooled at a rate of 87.5° C. / s to 8,750° C. / s, e.g., at least 1,750° C. / s to 8,750° C. / s, including 4,375° C. / s to 8,750° C. / s. Thus, the sintered LRMO material may be cooled from a heat treatment temperature (e.g., a sintering temperature) of at least 800° C. to a cooling bath temperature (e.g., a room temperature water bath at 25° C.) in 10 seconds or less, e.g., less than 500 milliseconds, including 400 milliseconds or less, 300 milliseconds or less, or 200 milliseconds or less. For example, the quenching may occur in 100 milliseconds to 400 milliseconds or 100 milliseconds to 200 milliseconds.
[0031] The quench bath may include a high heat capacity liquid solvent having an evaporation temperature less than about 200° C. For example, the quench bath may include a solvent such as water, oil, and / or alcohol. In some embodiments, the quench bath may include an additive configured to modify the surface of the LRMO material during quenching to improve the long-term chemical stability of the LRMO material. The additive may include an acid, an alcohol, and / or a dissolved carbon species, such as an acid, an alcohol, or a carbon species dissolved in water.
[0032] For example, the quench bath can be an aqueous quench solution including an acid additive, such as sulfuric acid, hydrochloric acid, nitric acid, oxalic acid, citric acid, acetic acid, phosphoric acid, orthophosphoric acid, and mixtures thereof, at about 0.01 to about 1.0 mol / L, such as about 0.1 to 1.0 mol / L or about 0.5 to 1.0 mol / L. The acid can be configured to stabilize the surfaces of the LRMO particles by reacting with and / or passivating dangling bonds and / or OH end groups of the LRMO powder particles that are quenched in the water containing the acid.
[0033] In some embodiments, acid quenching can form a spinel structure (e.g., a surface layer) on the surface of the quenched LRMO powder particles. The spinel structure can form a framework (or skeleton) that stabilizes the particles and can provide three-dimensional pathways for lithium diffusion. In particular, the acid causes an exchange of Li ions of the particles with H ions of the acid, resulting in a structural transformation at the surface of the particles, which forms a spinel surface layer.
[0034] In another embodiment, the quenching solution may include an alcohol and / or a hydrocarbon additive in addition to or in place of the acid additive, e.g., the alcohol may include isopropyl alcohol or other alcohols, and the hydrocarbon may include sugar, fructose, galactose, glucose, lactose, maltose, sucrose, and combinations thereof. In some embodiments, the quenching solution may include a hydrocarbon additive at about 0.01 to about 1.0 mol / L, e.g., about 0.1 to 1.0 mol / L or about 0.5 to 1.0 mol / L. The hydrocarbon may form an intimate amorphous carbon coating on the surface of the LRMO powder particles during the quenching process in the water containing the hydrocarbon. The carbon coating may be permeable to Li-ions, but impermeable to the electrolyte of the Li-ion battery. The carbon coating may also change volume during charging and discharging the battery, allowing for volume changes in the LRMO crystallites.
[0035] Rapid or ultrarapid quenching processes can produce quenched LRMO materials with crystal structures that provide unexpected robustness and electrical properties. In particular, the degree of crystalline order in quenched LRMO materials (e.g., lithium-rich lithium manganese nickel oxides) produced by quenching processes can provide performance characteristics suitable for use as cathode active materials in lithium-ion batteries that provide energy density and charge storage stability characteristics similar to cobalt-containing, high nickel content active materials.
[0036] The quenching process can produce a quenched LRMO material having a desired crystal structure and particle size. For example, the quenched sintered LRMO material can be a loose (or disaggregated) powder having an average particle size of about 1 μm or less, such as an average particle size ranging from about 0.02 μm to about 1 μm or from about 0.05 μm to about 0.5 μm. The quenched LRMO material can, in some embodiments, include crystalline phases and / or crystallites (or crystallites) having an average crystal size ranging from about 25 nm to about 500 nm, such as from about 50 nm to about 300 nm. Each powder particle can include one crystallite or more than one crystallite. The loose sintered and quenched powder particles can be incorporated into a binder (e.g., a carbon binder) to form a cathode electrode for a Li-ion battery.
[0037] The quenched LRMO material may be dried to form an LRMO active material (e.g., heat treated and quenched loose powder particles) having a hexagonal primary phase and a monoclinic secondary phase. Thus, the ratio of hexagonal phase content to monoclinic phase content is greater than 1, e.g., at least 2, e.g., 2-20. For example, the sintered and quenched LRMO material (e.g., dried active material) may have a superlattice structure including hexagonal primary phase layers spaced by intercalated layers of monoclinic secondary phase. Alternatively, the sintered and quenched LRMO material may include a hexagonal phase matrix including monoclinic phase nanodomains (i.e., domains having widths less than a micron). Mn and Ni may be homogeneously distributed within the crystal structure of the LRMO material (e.g., excess Mn, Ni, and Li are homogeneously and uniformly distributed in transition metal crystal lattice sites). For example, the crystalline grains of sintered and quenched LRMO materials exhibit a uniform distribution of Mn and Ni throughout the crystalline grain such that there are no Ni-rich or Mn-rich regions when imaged by high-angle annular dark-field (HAADF) energy dispersive X-ray spectrometry (EDS) (i.e., in an EDS elemental map of a HAADF tunneling electron microscope image). In some embodiments, the term "no Ni-rich or Mn-rich regions" in a crystalline grain means that there is no crystal volume in the crystalline grain that has a difference in the ratio of Ni and Mn atoms of more than 3% compared to the average ratio of Ni and Mn atoms in the entire crystal, over a volume of more than 3×3×3 nm.
[0038] The crystal structure of the as-formed active LRMO material may change upon electrochemical cycling. For example, when the active LRMO material is included as the active material in an electrochemical cell, after the first charge / discharge cycle, the monoclinic phase may no longer be present at detectable levels. It is believed that the monoclinic phase may have been consumed during the insertion and / or extraction of Li-ions.
[0039] Rapid precursor decomposition The LRMO materials can be formed from a variety of precursor materials. For example, the precursor materials can be organometallic compounds that include a metal, such as Li, Mn, and / or Ni, and a solubilizing agent, such as an organic ligand. For example, the precursor materials can include metal acetates, carbonates, nitrates, sulfates, and / or hydroxides.
[0040] In various embodiments, the LRMO material may be formed by pyrolyzing a precursor material, followed by sintering and quenching the resulting pyrolyzed LRMO material. The precursor material may include a gel formed via a sol-gel process. The inventors have found that rapid decomposition of the precursor material gel may improve the homogeneity of the LRMO material. For example, in the sol stage of the sol-gel process, stoichiometric amounts of Li, Mn, and Ni-containing precursors may be mixed with water to form an aqueous mixture. For example, stoichiometric amounts of Li(CH3COO)*2H2O, Mn(CH3COO)2*4H2O, and Ni(NO3)2*6H2O may be mixed to form an aqueous mixture. For example, in some embodiments, an all-acetate precursor or an all-nitrate precursor (i.e., nitrates of lithium, manganese, and nickel) may be used. In some embodiments, the mixture may include a 0.01 to 0.20 mole fraction excess of lithium acetate to compensate for lithium loss during processing.
[0041] The mixture can then be heated to form a precursor gel, for example, the mixture can be heated to a temperature in the range of about 90° C. to about 150° C., for example about 100° C., for a time sufficient for gelation to occur.
[0042] The gel is then pyrolyzed, e.g., the gel can be heated at a temperature and for a time sufficient to extract (e.g., evaporate and / or decompose) the solubilizing agent, e.g., organic ligands, and / or solvent of the gel to form the pyrolyzed LRMO material.
[0043] Pyrolysis can be carried out using conventional furnaces, such as muffle box furnaces and / or tube furnaces. However, such devices generally have slow heating and cooling rates, on the order of 1-10° C. / min, and do not utilize any type of direct radiative thermal energy input. Thus, conventional furnaces can require at least 8 hours of processing time and significant amounts of energy to form the pyrolyzed LRMO material.
[0044] According to various embodiments, a rapid (e.g., high rate) heating method is used to form the pyrolyzed LRMO material. For example, certain embodiments may utilize microwave radiation to thermally treat the LRMO precursor material (i.e., to rapidly decompose the LRMO precursor, which may be, for example, a gel precursor formed via a sol-gel process).
[0045] Microwaves are defined as electromagnetic radiation with wavelengths between 1 mm and 1 m. Widely applied domestic microwave ovens use microwave radiation with a frequency of about 2.45 GHz. Regulations limit the microwave frequencies that can be used for domestic and industrial applications. The mechanisms of microwave heating are broadly divided into two categories: 1) the flow of electric current under the external electric field generated by microwave radiation generates heat due to the ohmic effect, and 2) the dipoles present in ceramics reorient under the change of electric field, generating heat due to friction.
[0046] Microwave heating can reduce thermal processing (e.g., precursor pyrolysis) temperatures, can provide shorter heating times due to very rapid localized heating compared to conventional furnace heating processes, and can allow more efficient volumetric heating due to intimate mixing of the precursor materials than conventional furnace heating processes.
[0047] In some embodiments, microwave heating can be used to heat and decompose the precursor material to form the pyrolyzed LRMO material. For example, the precursor material can include ligands and / or metals that are highly susceptible to microwave radiation. Thus, various embodiments utilize microwave radiation to heat the precursor and / or precursor gel to very high temperatures in a very short time. It has also been found that microwave heating provides very homogeneous heat dispersion. Thus, by utilizing microwave radiation, the heating rate and the texture and / or structure of the resulting pyrolyzed LRMO material can be dramatically changed. For example, microwave heating of the precursor gel can result in a highly homogeneous pyrolyzed LRMO material. The pyrolyzed LRMO material can be in the form of an inorganic ash that is devoid of organic components (e.g., contains no carbon or contains an unavoidable amount of carbon). Thus, by microwave heating, the pyrolyzed LRMO material can be formed without the need for, or can be omitted from, a separate furnace calcination.
[0048] For example, the precursor gel can be provided to a microwave furnace where microwave radiation is used to decompose the gel to form pyrolyzed LRMO material. For example, microwave radiation can be used to heat the gel to a temperature of at least 350° C., e.g., about 350° C. to about 500° C., for a time sufficient to evaporate the ligands and / or solvents of the gel to form pyrolyzed LRMO material (e.g., LRMO inorganic ash). In various embodiments, pyrolyzed LRMO material can be formed using continuous or pulsed microwaves having a power level of 20,000 W or less per kg of material irradiated with microwaves for about 30 minutes or less, e.g., about 15 to 30 minutes. Thus, microwave-based heating processes can be configured to rapidly remove (e.g., vaporize and / or burn) organic components from the precursor species to form pyrolyzed LRMO material with improved structural features, such as, for example, homogenous cation and / or metal oxide distribution.
[0049] While microwave pyrolysis of precursor gels formed by sol-gel processes has been described above, in other embodiments, the precursors pyrolyzed by microwaves may be formed by other methods. For example, alternative precursor preparation methods may include mechanical milling / mixing methods, freeze-drying rotary evaporation, or co-precipitation methods. In one embodiment of the co-precipitation method, precursors containing hydroxides of Mn and Ni may be mixed with lithium carbonate and co-precipitated. Solid-state precursor materials may also be used, including, for example, Li2CO3 or LiOH, nickel oxides and manganese oxides. Such solid-state precursors may have an excess of lithium-containing precursors, between 0.01 and 0.20 mole fraction excess, to overcome loss of lithium content during processing. Precursors prepared by any of these methods may also be subjected to microwave pyrolysis to form pyrolyzed LRMO materials (i.e., LRMO inorganic ash).
[0050] The pyrolyzed LRMO material (i.e., LRMO inorganic ash) is then mixed and ground (e.g., milled) to form a precursor LRMO powder. The precursor LRMO powder is then heat treated (e.g., sintered) in any suitable heat treatment device, such as a furnace, such as a tube furnace or muffle box, to form a sintered LRMO material. For example, the precursor LRMO powder material can be heated (e.g., sintered) at a heat treatment temperature (e.g., at least 800° C., e.g., about 900° C.) for a time ranging from about 12 to about 24 hours, and then the sintered LRMO material is subjected to rapid or ultra-rapid quenching as described above to form a quenched LRMO material. The quenched LRMO material can then be dried and optionally ground (e.g., milled) again to form a LRMO active material (e.g., a cathode active material powder). This LRMO cathode active material powder is then mixed with a binder or other inert cathode material to form a cathode for a Li-ion battery.
[0051] According to various embodiments, the method of forming LRMO materials includes a combination of rapid heating (e.g., microwave heating) for at least a portion of the heat treatment combined with rapid or ultra-rapid quenching to produce LRMO materials with unexpectedly high performance. In particular, this process can produce LRMO materials with no or substantially no nickel or nickel oxide segregation at the surface of the particles (crystallites), which can be observed using transmission electron microscopy, as well as a high degree of atomic / cationic disorder / homogeneity, which can be quantified using X-ray diffraction. The combination of these materials can contribute to producing cathode active materials that exhibit low or no capacity fade over 100 to 1000 charge / discharge cycles, substantially reduced or eliminated loss in average discharge voltage during cycling, and rate capabilities suitable for commercial use.
[0052] According to various embodiments, embodiment methods including microwave heating and / or rapid / ultra-rapid quenching steps can be used to form LRMO active materials that do not suffer from the chemical instability of conventional LRMO materials. In particular, rapid / ultra-rapid quenching steps can be used to form LRMO active materials with reduced Ni surface segregation and improved structural homogeneity compared to conventional LRMO materials that are sintered and then slowly cooled. In various embodiments, the microwave heating process described above can be used in conjunction with rapid / ultra-rapid quenching to form LRMO active materials. For example, pyrolyzed LRMO materials formed using microwave decomposition can be sintered and then subjected to a rapid or ultra-rapid quenching process.
[0053] In one embodiment, the cathode electrode (i.e., positive electrode) includes LRMO active material including a powder embedded in a binder. The powder has an average particle / agglomerate size in the range of about 0.1 μm to about 10 μm and an average crystallite (i.e., crystallite) size in the range of about 25 nm to about 500 nm. In one embodiment, the particles of the LRMO active material powder can have at least one of a spinel surface layer, a carbon coating (e.g., from a hydrocarbon additive in the quench bath), and / or passivated oxygen bonds at the surface (e.g., from an acid additive in the quench bath). The cathode electrode can be included in a battery, such as, for example, a lithium ion battery, which also includes an anode electrode (i.e., negative electrode), an electrolyte, and a separator.
[0054] In one embodiment, the cathode electrode active material has the formula Li x (M y Ni 1-y ) 2-xO2, where x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1. The active material may include a layered hexagonal (rhombohedral) phase and a monoclinic phase, at least prior to initially subjecting a battery including the cathode electrode to electrochemical cycling. The active material may exhibit at least one of the following: (i) an intensity ratio of the (006)+(102):(101) X-ray diffraction peaks greater than 0.32, e.g., 0.33 to 0.346, and / or (ii) a ratio of the (003) to (104) X-ray diffraction peaks greater than 2, e.g., 2.01 to 2.575, and / or (iii) a specific capacity at first discharge (e.g., C / 2 rate) of at least 200 mAh / g, e.g., 200 to 230 mAh, when the cathode electrode is included in a lithium ion battery. / g, and / or (iv) when the cathode electrode is included in a lithium ion battery, the lithium ion battery exhibits less than 10% loss in average discharge voltage after 100 charge / discharge cycles at a C / 20 rate, and / or (v) when included in a positive electrode of a lithium ion battery, the capacity fade is less than 10%, e.g., less than 5% (e.g., 0-4% capacity fade or capacity gain) for at least 100 charge / discharge cycles, e.g., more than 200 C / 5 charge / discharge cycles. In one embodiment, the lithium ion battery may include lithium or graphite as the anode electrode.
[0055] In one embodiment, the average discharge voltage of the battery (e.g., a lithium ion battery) does not decrease by more than 5% (e.g., 0-4%) after 50 C / 20 (charge)-C / 2 (discharge) charge / discharge cycles, and / or the discharge capacity of the battery is greater than 80% of its initial capacity after 800 C / 20-C / 2 charge / discharge cycles. EXAMPLES
[0056] Formula Li x (M y Ni 1-y ) 2-xLRMO powder with O2 (where x=1.16, y=0.7) was produced using the following method. In particular, a precursor material gel was produced using a sol-gel solid state synthesis method. The synthesis of the sol involved forming an aqueous mixture containing stoichiometric amounts of Li(CH3COO)*2H2O, Mn(CH3COO)2*4H2O, and Ni(NO3)2*6H2O. The mixture was heated at 100°C until a gel was formed. The gel was poured into an alumina crucible and calcined at 400°C for 90 minutes to obtain an ash devoid of organics. The resulting ash was ground in the crucible and re-calcined at 500°C for 3 hours, then naturally cooled and re-ground, after which the powder was sintered at 900°C for 24 hours and quenched. All sintering was performed in a box furnace at ambient draft conditions. All quenching was performed after heating at 900°C for 12-24 hours.
[0057] Figure 1 is a photograph of a rapid quenching system 100 according to various embodiments of the present disclosure. Figure 2 includes four sequential time-lapse video capture images taken at 30 frames per second illustrating the rapid quenching process according to various embodiments of the present disclosure.
[0058] With reference to Figures 1-2, the LRMO material was fed into a tube furnace 110 where the material was heated to 900°C. The heated LRMO material was removed from the tube furnace and quenched to room temperature in a quench bath 120. The tube furnace 110 rotates during operation such that its contents are instantly discharged into the quench bath 110. The time interval between the time the LRMO material exits the furnace 110 at 900°C and the time it is quenched to room temperature takes less than 500 milliseconds, e.g., less than 200 milliseconds, to form the LRMO active material. After quenching, the LRMO material was filtered from the water of the quench bath 120 and dried in a vacuum oven.
[0059] In a first comparative example, the LRMO material was slowly cooled in the furnace 110 after sintering at 900°C. In a second comparative example, the LRMO material was cooled by discharging onto a metal plate after sintering. In a third comparative example, the LRMO material was first slowly cooled to room temperature and then inserted into the tube furnace 110 for the ultra-rapid quenching process, where it was held at 900°C for 30-120 minutes before being subjected to the ultra-rapid quenching process.
[0060] In another example, LRMO powders were formed using a rapid precursor decomposition process. In particular, the sol-gel precursor material described above was decomposed using microwave radiation to form LRMO powders with improved component distribution. In particular, application of microwave radiation caused rapid evaporation of the organic components of the precursor material as they absorbed the microwave energy. Thus, the LRMO components were homogenously mixed at the molecular level due to the thermal energy generated by the microwave radiation. The resulting LRMO powders were then sintered at 900°C for 12-24 hours, followed by ultra-rapid quenching as described above.
[0061] Several larger batches (up to 1 kg) of cathode material were produced both with and without microwave radiolysis and ultra-rapid quenching.
[0062] Material properties 3-4 show Li according to various embodiments of the present disclosure. x (M y Ni 1-y ) 2-x 3A and 3B are graphs of X-ray diffraction (XRD) patterns for O2 (where x=1.2 and y=0.75) material. The XRD pattern in FIG. 3 was obtained from a layered LRMO active material that was not rapidly quenched by immersion in water, and the XRD pattern in FIG. 4 was obtained from a layered LRMO active material that was rapidly quenched by immersion in water.
[0063] Evaluation of the XRD patterns shows that the LRMO material has the expected space group associated with the hexagonal (e.g., rhombohedral) phase LiNiO2 (R-3m) and the space group associated with the monoclinic phase Li2NiO3 (C2 / c).
[0064] FIG. 5 shows Li SiO 2 nanoparticles processed using 5 minutes of microwave heating of the sol-gel precursor material prior to a high temperature calcination step according to various embodiments of the present disclosure. x (M y Ni 1-y ) 2-x 5 is a graph showing X-ray diffraction results for LiNiO2 (where x=1.16 and y=0.7) material. Referring to FIG. 5, of significant interest is the fact that the microwave-decomposed material has an X-ray diffraction pattern obtained that is consistent with being a highly crystallized and optimized material, including the space group (R-3m) associated with the rhombohedral phase LiNiO2 and the space group (C2 / c) associated with the monoclinic phase Li2NiO3. Thus, this material is suitable for forming LRMO materials using 900° C. annealing and rapid and / or ultra-rapid quenching as described above.
[0065] FIG. 6 shows Li treated using microwave heating and ultra-rapid quenching according to various embodiments of the present disclosure. x (M y Ni 1-y ) 2-x 6 is a graph showing X-ray diffraction results for O2 (wherein x=1.16 and y=0.7) material. Referring to FIG. 6, all expected peaks are present and well defined.
[0066] 7A is a prior art example from the literature (H. Zheng et al., "Recent developments and challenges of Li-rich Mn-based cathode materials for high-energy lithium-ion batteries," Materials Energy Today, Volume 18, December 2020, pp. 100518) of a tunneling electron microscopy (TEM) high-angle annular dark-field imaging (HAADF) atomic map micrograph of a representative LRMO material that was not subjected to rapid quenching prior to electrochemical cycling of the material. As can be seen from these micrographs, the initial LRMO material has significant nickel and manganese segregation in the grains.
[0067] 7B are TEM HAADF atomic map micrographs of the resulting LRMO material that was subjected to rapid quenching prior to electrochemical cycling of the material, according to various embodiments of the present disclosure. As can be seen from these micrographs, the LRMO material does not have significant nickel / manganese segregation in the particles. Thus, rapid or ultra-rapid quenching reduces or eliminates nickel segregation to the particle surface, and nickel and manganese are homogeneously mixed in the bulk LRMO material.
[0068] Crystal homogeneity, cationic disorder and surface passivation One way to assess the degree of metal cation disorder in a material is to use the ratio of peak intensities in the X-ray diffraction pattern. In particular, the ratio of the intensity of the (003) peak to the (104) peak is commonly known as an approximate measure of electrochemical activity in mixed cation materials with this predominantly layered crystal structure, while the ratio of the sum of the intensities of the (006) and (102) peaks to the intensity of the (101) peak is an indicator of cationic disorder. On this basis, materials that have undergone both microwave treatment during the decomposition step and subsequent ultra-rapid quenching exhibit significantly higher electrochemical activity and a lower degree of cationic order (and therefore a higher degree of cationic disorder) than slowly cooled materials.
[0069] [Table 2]
[0070] Table 2 shows the XRD peak intensity ratios for comparative LRMO materials (row 1) that were subjected to slow quenching after calcination, and for example LRMO materials (row 2) that were subjected to ultra-rapid quenching after calcination. Both materials have the formula Li x (M y Ni 1-y ) 2-xO2, where x=1.2 and y=0.75. Importantly, the ultra-rapidly quenched materials of the examples exhibit XRD characteristics that indicate an increase in atomic disorder in the material, with significantly higher electrochemical activity and higher cationic disorder / metal oxide homogeneity than the comparative example materials. In particular, the example materials show an increase in the ratio of the sum of the intensities of the (006) and (102) peaks to the intensity of the (101) peak, in this case about 9%. This significant increase in cationic disorder represents a situation in which Ni and Mn atoms are more thoroughly mixed (and therefore less grouped) in the material. For this reason, such example materials may be referred to as "cation-disordered lithium-rich lithium manganese nickel oxides," and these data show that different states of matter may be formed based on the processing conditions used, particularly the cooling rates used.
[0071] Electrochemical Testing The synthesized cathode material was mixed with Super-P carbon black and polyvinylidene fluoride (PVDF) in a ratio of 8:1.2:0.8 to make 80% of the total mass of active material. The resulting blend was then mixed into a minimum amount of about 15 mL of N-methyl-2-pyrrolidone and subjected to a 10-minute ultrasonic treatment step after 1 hour, after which the resulting slurry was mixed on a 100°C hotplate for a minimum of 30 minutes and spray-coated onto a 10×10 cm, 10 μm thick aluminum foil heated to a temperature above 100°C. It was dried overnight in an oven at 70°C in air and punched out with a biopsy punch. These punches were then used to make 2032 coin cells containing lithium foil as the anode, 1.0 M LiPF6 50 / 50 ethylene carbonate / dimethyl carbonate solution as the electrolyte, a Celgard battery separator, a 0.5 mm stainless steel spacer, and a corrugated spring on the cathode side to ensure mechanical contact within the cell; each coin cell was assembled and sealed using a coin cell press in a dry, low-oxygen argon atmosphere.
[0072] Electrochemical performance studies of the coin cells fabricated by the above process were performed using a low current Neware or bio-logic battery tester to perform potential-limited galvanostatic testing at constant current. The cells were cycled under constant current charge / discharge conditions from 4.8 to 2 V at rates ranging from C / 20 to C / 2.
[0073] FIG. 8A shows the results of the LRMO material (Li) that was not microwave-treated or rapidly quenched (in this case, cooled relatively slowly on a metal plate). x (M y Ni 1-y ) 2-x FIG. 8A is a graph of specific capacity versus cell potential for a comparative example of O2 (where x=1.16 and y=0.7), and FIG. 8B is a graph of specific capacity versus cycles for the above comparative example.
[0074] 8A and 8B, it can be seen that the slowly cooled material has poor capacity and capacity retention. After 50 full charge / discharge (C / 2 rate) cycles, the material obtained a specific capacity of 120 mAh / g at C / 20 rate, which is far below the theoretical performance of the material. Furthermore, the average discharge potential was lower than 3 V after 30 cycles, and there was substantial voltage fade in the material.
[0075] Figure 9A is a graph showing cell potential vs. specific capacity during break-in cycling of the ultra-rapidly quenched material, Figure 9B is a graph showing cell potential vs. specific capacity over time for the ultra-rapidly quenched material, and Figure 9C is a graph showing specific capacity vs. cycle at a C / 20 rate over multiple cycles for an example cell including a LRMO active material according to some embodiments of the present disclosure. Figure 9D shows extended cycling of the example LRMO material, which shows that over 150 C / 5 cycles, the material exhibits less than 10% capacity fade for all three C / 20 reference cycles (this occurs at cycles 56, 107, and 158).
[0076] Compared to the comparative material shown in Figures 8A-8B, the example LRMO cathode materials made using ultra-rapid quenching showed superior performance, as shown in Figures 9A-9C. The electrochemical performance data shown in Figures 9A and 9B demonstrate both: (a) that high performance materials can be produced on a meaningful scale, and (b) that these materials have performance characteristics comparable to or better than those produced in much smaller batches. Notably, the voltage profile has an exaugurated and desirable inflection after roughly 100 mAh / g of discharge capacity compared to materials made using slower cooling methods. The voltage just above this inflection point shows virtually no "sag" or loss during cycling, an improvement over materials made using slower transfer techniques. This suggests that the ultra-rapid cooling approach of gravity-driven transfer from a furnace to a quenching environment in less than 200 milliseconds is desirable when combined with precursors that are rapidly decomposed via microwave irradiation.
[0077] FIG. 10A shows the results of the LRMO active material (Li x (M y Ni 1-y ) 2-x FIG. 10B is a graph showing specific capacity versus cell potential for a comparative cell containing LiO2 (where x=1.16 and y=0.7), FIG. 10B is a graph showing specific capacity versus cycle number for the cell of FIG. 10A, and FIG. 10C is a graph showing specific capacity versus cycle number for the cell of FIG. 10A that was not ultra-rapidly quenched, but was water-quenched LRMO active material (Li x (M y Ni 1-y ) 2-x 10A is a graph showing cell potential versus specific capacity for the first and 50 C / 2 discharge cycles for an example cell containing 02 (where x=1.16 and y=0.7) (the material was not removed from the furnace environment and quenched for several seconds), and FIG. 10D is a graph showing specific capacity versus cycle number for the cell of FIG. 10C. None of the active materials were microwave treated.
[0078] Both the comparative and example cells were cycled twice at both charge and discharge currents at a rate of about C / 20 to condition the cathode material. This was followed by 25 cycles at a charge rate of C / 20 and a discharge rate of C / 2. A set of 27 cycles was referred to as one round of cycling, and all cells were subjected to this regime twice. As can be seen from Figures 10A-10D, the rapidly quenched example material has improved capacity and capacity retention compared to the comparative material. After 50 full charge / discharge cycles, the example material obtained a specific capacity of nearly 230 mAh / g at a C / 2 rate, which is much better than the comparative example, which shows a much lower capacity and a lower average discharge voltage. Thus, the example materials (a) showed a significant increase in capacity over 50 cycles, (b) did not exhibit the commonly reported excessive voltage fade (the average discharge voltage of the cell drops significantly with abuse), and (c) exceeded 250 mAh / g after 25 cycles at a C / 20 discharge rate and exceeded 230 mAh / g after 50 cycles (at a C / 2 rate), with less than 10% loss in average voltage during discharge. The specific capacity increases by 20-25% over 50 full C / 20-C / 2 charge / discharge cycles. In contrast, the comparative example materials had much poorer performance, including specific capacity values below 100 mAh / g.
[0079] FIG. 11A shows microwave digested and rapidly quenched Li according to various embodiments of the present disclosure. x (M y Ni 1-y ) 2-x FIG. 11B is a graph showing specific capacity versus cell potential for an example cell including O2 (where x=1.16 and y=0.7) active material, and FIG. 11B is a graph showing specific discharge capacity versus cycle at C / 20 and C / 2 rates for an example cell of FIG. 11A.
[0080] Thus, as shown in Figures 11A-11B, the microwave decomposition process combined with rapid thermal quenching results in a much more electrochemically stable material. The combination of microwave treatment and rapid quenching results in a significantly reduced voltage drop and stable discharge capacity over approximately 200 cycles (where the commonly used coin cell tests fail) compared to the comparative cell material.
[0081] The synthetic LRMO active material (i.e., sintered and quenched loose powder) was mixed with Super-P carbon black and polyvinylidene fluoride (PVDF) in a ratio of 8:1.2:0.8 to make 80% active LRMO by total mass. The resulting blend was then mixed in about 15 mL of N-methyl-2-pyrrolidone for a minimum of 1 hour. Two 10 minute sonication steps were then performed, after which the resulting slurry was mixed on a 100°C hotplate for a minimum of 30 minutes, and then spray coated onto a 10x10 cm, 10 μm thick aluminum foil heated above 100°C. The foil was dried overnight in an oven in air at 70°C, and then sampled into a round electrode disk. The resulting punch was then used to make 2032-type coin cells that contained a lithium foil anode, a 1.0 M LiPF6 50 / 50 ethylene carbonate / dimethyl carbonate solution as the electrolyte, a Celgard battery separator, a 0.5 mm stainless steel spacer, and a corrugated spring on the cathode side to ensure mechanical contact within the cell. Each coin cell was assembled and sealed using a coin cell press in a dry, low-oxygen argon atmosphere.
[0082] The coin cells made by the above process were subjected to constant current potential limiting galvanostatic testing using a LAND battery tester. A minimum of three cells per variation were cycled between 2.0V and 4.8V at ambient temperature. To condition the cathode material, they were cycled twice at both charge and discharge currents at approximately C / 20 rates. The cells were then charged and discharged 25 times at a charge rate of C / 20 and a discharge rate of C / 2. These 27 cycles can be referred to as one round of cycling, and all cells were subjected to two rounds of cycling.
[0083] FIG. 12A shows the change in the charge transport coefficient of the x=0.25 sample (i.e., Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) 12B-12D show the full charge and discharge curves of coin cells containing the 25Hq, 25Lq and 25Mq samples, respectively. FIG. 13A shows the specific discharge capacity of the x=0.17 sample over a series of cycling, and FIG. 13B-13D show the full charge and discharge curves of coin cells containing the 17Hq, 17Lq and 17Mq samples, respectively. FIG. 14A shows the specific discharge capacity of the x=0.10 sample over a series of cycling, and FIG. 14B-14D show the full charge and discharge curves of coin cells containing the 10Hq, 10Lq and 10Mq samples, respectively.
[0084] Table 3 below shows the discharge capacity (DC) over a series of cycling along with the C / 20:C / 2 ratio for DC28 / DC27. The rate capability was evaluated by taking the ratio of the C / 20 discharge capacity and the C / 2 discharge capacity (the discharge capacity of the 27th and 28th cycles). Note that discharge cycles 1, 2, and 28 were at C / 20 rate, and discharge cycles 3, 27, and 54 were at C / 2 rate.
[0085] [Table 3]
[0086] 12A-12C, the x=25 samples synthesized with different cooling methods showed different relative charge capacities at the first charge 4.5 V plateau. In particular, the 25Hq plateau accounted for 60.7% of the initial charge capacity, the 25Lq plateau accounted for 44.4%, and the 25Mq plateau accounted for only 34.5%.
[0087] The initial capacity of the 25Hq was 186mAhg for the x=0.25 sample. -1 With 25Mq, 127mAhg -1 As can be seen from Table 3, all x=0.25 samples except for 25Mq showed improved capacity over the course of cycling. 25Hq showed the highest capacity of all three samples. The 25Mq sample also showed severe voltage fade over the course of cycling, with the voltage dropping below 3V. The 25Hq and 25Mq samples also had an inflection point at 2.8V on their discharge curves, but they did not show such severe voltage fade. No voltage fade was seen in the C / 20 discharge of the 25Hq and 25Lq samples, but the C / 20 discharge of the 25Mq sample did experience voltage fade. The average discharge voltage of the 0.25 samples reflected these voltage fades, with the 25Mq having the lowest average voltage over the course of cycling and the 25Lq having a slightly higher average discharge voltage than the 25Hq.
[0088] In terms of rate capability, as can be seen from Table 3, the C / 20:C / 2 ratios for 25Hq, 25Lq and 25Mq were 1.19, 1.25 and 1.39, respectively.
[0089] 13A-13D, the charging profile of the x=0.17 sample had a more classical single flat 4.5 V plateau on the first charge, which accounted for approximately 56.8% of the initial charge capacity, while the 17Lq and 17Mq samples showed a less defined 4.5 V plateau, which accounted for approximately 20% of the initial charge capacity in both cases.
[0090] The capacity of all x=0.17 samples was approximately 10mAhg during the first two C / 20 discharges. -1 As can be seen from Table 3, the second C / 20 discharge showed a capacity increase of 31%, 71% and 91% for 17Hq, 17Lq and 17Mq, respectively. There was a nearly uniform voltage decay behavior for all three samples, with the average plateau voltage decreasing by roughly 0.4V over the series of cycling. However, no voltage decay was observed in the C / 20 discharge curves of these samples. The x=0.17 sample also has a similar average discharge voltage over time. The main difference is how the average voltage of 17Mq increases in the first cycle, but in the second cycle, which matches the voltage fade trend of 17Hq and 17Lq.
[0091] 14A-14D, for the charging profile of the x=0.10 sample, the 10Hq charging profile is different from the 10Lq and 10Mq samples, while the 10Lq and 10Mq samples have similar profiles. All three samples have a persistent inflection point at 4.5V, but only the 10Hq sample has a clear 4.5V plateau, where the inflection point of the 10Hq disappears, and the inflection points of the 10Lq and 10Mq samples persist until the 54th cycle. The inflection point of the 10Mq sample is the most prominent.
[0092] As can be seen from Table 3, all of the x=0.10 samples lost 5 mAhg during the first C / 20 cycle. -1The 10Hq and 10Mq samples experienced an initial capacity increase of the order of 0.10 V, followed by 300%, 60%, and 67% capacity improvements for the 10Hq, 10Lq, and 10Mq samples, respectively, at the second C / 20 discharge. By the end of the first C / 2 discharge, the capacities of all x=0.10 samples exceeded or caught up with the initial C / 20 capacity. Over the course of the second C / 2 discharge series, the 10Hq showed 197% and 50% capacity increases, the 10Lq showed 25% and 16% capacity increases, and the 10Mq showed 36% and 20% increases at the first and second discharges, respectively. The discharge plateaus for the 10Lq and 10Mq began at approximately 3.0 V, whereas the plateau for the 10Hq sample began at 3.2 V, and the voltage behavior over the cycling series for the 10Hq was different from the 10Lq and 10Mq. The voltage behavior of all x=0.10 samples was rate dependent, and the average discharge voltage of the C / 20 discharges of all three samples increased over the cycling series, however, the C / 2 discharges of the 10Lq and 10Mq samples showed signs of voltage decay, but the 10Hq did not.
[0093] In addition, the 10Lq and 10Mq samples had an inflection point at 2.2 V, which was unique in the C / 20 discharge curves. These voltage behaviors of the x=0.10 sample showed that the average discharge voltages of the 10Lq and 10Mq were higher than that of the 10Hq, but the degree of voltage fade was also greater.
[0094] For rate capability, the C / 20:C / 2 ratios for the 10Hq, 10Lq and 10Mq samples were 1.27, 1.60 and 1.67, respectively, as shown in Table 3. It is noted that the effective charge and discharge at each cycle evolves significantly with cycling, which makes the DC28 / DC27 ratio for the 10Hq effectively the C / 10:C / 1 ratio.
[0095] Various phase changes over the test series are evident in the voltage profiles observed during cycling. The expected voltage plateau seen in the x=0.25 sample suggests that the expected classical phase change occurred.
[0096] 15A-15I are graphs showing normalized and offset XRD patterns of LRMO powders before and after cycling for the 25Hq, 25Lq, 25Mq, 17Hq, 17Lq, 17Mq, 10Hq, 10Lq and 10Mq samples, respectively.
[0097] Referring to Figures 15A-15I, the XRD patterns after cycling for all x=0.25 samples show a loss of the 2θ=22° superlattice peak, indicating that segregation of transition metals may have occurred to equilibrate the structure. However, all other R-3m indexed peaks remain, suggesting that the overall structure is preserved. Similar results are seen in the x=0.17 and 10Hq samples. This loss of transition metal ordering is associated with loss (or deficiency) of oxygen and lithium and thus capacity loss, whereas the increase in capacity seen in Figures 12A-14C indicates that this is not the case for these samples. Thus, these data suggest that segregation of transition metals does not necessarily result in capacity loss.
[0098] Although the 10Mq and 10Lq samples still have some peaks visible at 22°, the 10Mq sample has a substantially different crystal structure after cycling testing, further suggesting that the electrochemical phase changes seen in Figures 14A-14C are not the same as those seen in the cycling data of Figures 12A-13C. Another phase change seen in Figures 10Lq and 10MQ suggests that there is a synthesis limit for LRMO that exists somewhere between nickel contents of 0.17>x>0.10.
[0099] Figure 16 includes SEM micrographs at 50,000 times magnification (50kx) of cathodes spray coated with 25Hq, 25Lq and 25Mq samples before and after cycling. Figure 17 includes SEM micrographs at 50,000 times magnification of cathodes spray coated with 17Hq, 17Lq and 17Mq samples before and after cycling. Figure 18 includes SEM micrographs at 50,000 times magnification of cathodes spray coated with 10Hq, 10Lq and 10Mq before and after cycling.
[0100] With reference to Figures 16-18, the morphology (or form) of the cathodes as fabricated and after cycling was uniform for the x=0.25 and x=0.17 samples, as seen in Figures 16 and 17. The morphology of the x=0.10 sample was not consistent, as seen in Figure 18. The 10Hq was consistent with the higher nickel content samples, while the 10Lq and 10Mq were consistent with each other. All samples had consistent morphologies before and after cycling, and there was no evidence that the surface structure or particle morphology changed as a result of electrochemical cycling.
[0101] Both the nickel content and the quenching method affect the structure and electrochemical behavior of LRMO cathodes. In general, materials synthesized with higher nickel content and / or more rapid quenching rates have higher capacity and more classical voltage behavior, although results can be subtle.
[0102] The XRD patterns of the LRMO powders show a dependence of structure on both nickel content and quenching method. Slight crystallographic variations in samples of various nickel contents are expected and were observed in the x=0.25, x=0.17 and 10Hq samples. The XRD patterns of 10Lq and 10Mq had numerous secondary peaks, whereas the 10Hq pattern did not. The secondary peaks seen in the 10Lq and 10Mq patterns match those seen in the XRD patterns of the 25q and 17Mq samples. These examples suggest that the quenching rate is important in determining the structure, layer content and layer purity.
[0103] The secondary layered phase seen in many samples may be the result of localized relatively nickel-rich inhomogeneities and correspondingly larger lattice parameters. Splitting of the (110) peak is present in the XRD patterns of all samples except 25Hq and 25Lq, indicating that slower quenching results in nickel inhomogeneities. The XRD patterns of the 25Mq and 17Mq samples have additional secondary peaks at (101), (104), and (107) seen in the 10Lq and 10Mq samples. It should be noted that the (104) secondary peak for 25Mq and 10Lq may be due to impurities (or contaminants or contamination). These additional peaks, although varying, occur in all metal-quenched samples, indicating how the structure is dependent on both nickel content and quenching. These data support the notion that slower quenching methods result in the formation of segregated nickel-rich phase regions as well as impurities in the material, thus determining the local ordering of nickel in the sample, regardless of Ni content. Figure 24 shows an outline of the proposed structure for the secondary layered phase.
[0104] Ni 2+It is believed that the less Ni present, the less localized lattice expansion occurs, since the Ni ions have a larger ionic radius than the Mn ions. The higher nickel content of the samples results in a smaller lattice parameter due to more favorable ordering with less long-range ordering to disperse the nickel ions. Quenching these samples rapidly preserves the long-range ordering and smaller lattice parameter, while slower quenching results in impurity nucleation and nickel inhomogeneity, both of which distort the average lattice parameter. The intersection point observed in FIG. 26B for the lattice parameter "a" is at x=0.11, which further suggests a synthesis limit of 0.17>x>0.11.
[0105] The electrochemical behavior of the samples was affected by both the nickel content and the quenching method. The first charge behavior of the material is an indicator of purity and capacity, with the higher performing materials known to exhibit a single strong plateau consistent with a phase transition via nickel-catalyzed oxygen and lithium loss.
[0106] 19A-19C are graphs showing smoothed spline fits of dQ / dV versus V for the first charge cycle of the x=0.25, x=0.17, and x=0.10 samples.
[0107] With reference to Figures 19A-19X, the 4.5V peak seen in the dQ / dV plots indicates that all samples have some initial 4.5V plateau. However, Figures 12A-14C show that only some samples have an inflection point at 4.5V on later charges. This suggests that all samples initially undergo a similar phase transformation, but the persistence of the inflection point in some samples suggests that the reaction is not necessarily able to go to completion during the first charge. Samples with secondary peaks in the pattern are similar to those with inflection points at later cycles and therefore may be related. This is further supported by how higher nickel content results in a secondary layered phase peak present to the left of the main peak. Some samples, such as the 25Mq and 10Lq, show signs of rock salt impurities, but this impurity does not exclude the possibility of some other phase transition. Nevertheless, these changes occur over a larger number of cycles and gradually fade, suggesting that the samples are not yet fully and irreversibly transformed.
[0108] The presence of inflection points in the non-water-quenched samples, but not in the 10Hq, provides further evidence that these inflection points are related to phase homogeneity. The 10Hq sample begins at these inflection points, and by the 54th cycle its charge profile is more similar to the x=0.17 sample than it initially resembles to the x=0.10 sample. Thus, these data are consistent with the development of nickel homogeneity that prolongs the 4.5V phase transition.
[0109] 20A-20C are graphs showing smoothed spline fits of dQ / dV vs. V for the second charge cycle of the x=0.25, x=0.17 and x=0.10 samples. FIGs. 21A-21C are graphs showing the first and last C / 2 discharges of the 25Hq, 25Lq and 25Mq samples, and FIG. 21D is a graph showing the average discharge voltage per cycle over a series of cycling for the 25Hq, 25Lq and 25Mq samples. FIGs. 22A-22C are graphs showing the first and last C / 2 discharges of the 17Hq, 17Lq and 17Mq samples, and FIG. 22D is a graph showing the average discharge voltage per cycle over a series of cycling for the 17Hq, 17Lq and 17Mq samples. 23A-23C are graphs showing the initial and final C / 2 discharges of the 10Hq, 10Lq and 10Mq samples, and FIG. 23D is a graph showing the average discharge voltage per cycle over a series of cycling for the 10Hq, 10Lq and 10Mq samples.
[0110] The discharge profiles of the samples also show that cycling behavior over time is affected by the nickel composition and quenching method. With reference to Figures 20A-20C, the peaks of the water quenched samples are initially at lower voltages on average than the liquid nitrogen and metal quenched samples, suggesting that nickel heterogeneity affects the voltage. The average discharge voltage of the water quenched samples is at equilibrium lower than the other samples of the same composition, except for the 25Mq. The dQ / dV patterns of the 17Lq and 17Mq, and Figures 21A-23D, show how the discharge profiles change over time to different behaviors. The voltage of the x=0.17 sample has the most homogeneous voltage behavior, but also shows the greatest degree of voltage decay. The exception to this is the 25Mq sample, which shows voltage decay over the course of cycling, while the x=0.10 sample shows a voltage increase for the C20 discharge and a voltage fade for the C / 2 discharge. It is also important to note that the average voltage fade shown for most samples is due to a change to higher capacity at these voltages as opposed to degradation of the samples. The apparent differences in discharge behavior seen in the samples suggest that differences in quenching rates are manifested in different electrochemical reactions.
[0111] The voltage decay for the 25Hq and 25Lq is slight compared to that of the x=0.17 sample, and their associated voltage plateaus are also at different voltages. The smaller 25Hq and 25Lq voltage decays, associated with the 3 V plateau, are roughly consistent with a phase change to a spinel-like phase over the cycling series. The more severe voltage decay for the x=0.17 sample is also roughly consistent with a phase change to a spinel-like phase. In both cases, but especially in the case of the x=0.17 sample, the voltage plateaus are consistent with the Ni-rich phase in a manganese-rich environment. 2+ / 3+ / 4+The plateaus are close to the average voltage of the redox (or reduction-oxidation) phase, suggesting that these plateaus are caused by nickel redox and therefore nickel distribution. This voltage loss and nickel redistribution is roughly consistent with the evolution to a spinel-like phase, with the main discrepancy being the increase in capacity, which is associated with both capacity gain and loss, and which is generally associated with significant structural degradation. Thus, the voltage decay of the structurally robust 25Hq, 25Lq and x=0.17 samples cannot be entirely attributed to the evolution to a spinel-like phase.
[0112] Also, the change to a spinel-like phase does not explain the different behavior between discharge rates, especially for the x=0.10 sample. The C / 20 discharge of the x=0.10 sample starts at a voltage similar to the quenched sample and increases in voltage through cycling, while the C / 2 discharge of the x=0.10 sample experiences some degree of voltage fade. The lower potential of the sample can be attributed to the higher manganese concentration and subsequently the lower nickel redox potential, but the inconsistent voltage behavior is not fully explained as being due to the formation of a spinel-like phase, especially when considering the rapid increase in capacity. In contrast to the lower manganese concentration of 25Mq, the capacity loss and faster voltage decay are indicative of the formation of a spinel-like phase. These factors (however practically the discharge voltage plateau begins at 3V) are consistent with the voltage decay mechanism of the change to a spinel-like phase. Phase impurities that evolve during the slow quench would make 25Mq more sensitive to the change to a spinel-like phase. The voltage plateau of 25Mq is due to the presence of Mn 3+ / 4+The discharge plateau of 10Lq and 10Mq is similar to that of 25Mq beginning at 3V, suggesting that these samples may have undergone some degree of transformation to a spinel-like phase. The XRD of all samples except 10Mq have peaks indicative of an R-3m layered structure, further suggesting that the transformation to a spinel-like phase is not the entire reason for the voltage fade or change in capacity.
[0113] Figure 24 is a schematic showing how the inclusion of phase impurities in a 25Mq sample with R-3m structure and lattice parameter a'>a results in secondary peaks as seen to the left of the 25Mq(104) peak. As shown in Figure 24, the nickel redox that results in these plateaus suggests that the nickel content is homogeneous over time.
[0114] Electrochemical cycling data for the LRMO cathodes showed consistent increases in capacity, except for the 25Mq. The x=0.25 sample showed a small gain in capacity, while the x=0.17 sample showed a more significant increase, and the x=0.10 sample showed an even more significant increase. The percent increase in specific capacity with cycling was inversely correlated with nickel content, regardless of quenching method. The largest increases in capacity were observed in the 10Hq sample, as well as the 10Mq and 10Lq samples. This relationship is at least partially driven by the homogenization of nickel content through the "electrochemical annealing" process over the course of cycling, as impurities are associated with nickel inhomogeneities.
[0115] Comparative XRD of the cathode material after cycling versus the original cathode material shows very similar behavior for all samples except 10Lq and 10Mq, where the transition metal superlattice peak disappears after cycling. The 10Lq has the superlattice peaks retained after cycling, while the 10Mq sample shows the appearance of several new peaks, a notable difference between the two samples. This difference further indicates the importance of the quench rate, as there is a lower synthetic limit for LRMO (where 0.17>x>0.10) at the slower quench conditions. However, the behavior of the 10Hq sample is different, indicating that the more rapid quenching of the sample results in the stability and long-term performance associated with the higher Ni content samples.
[0116] Electrochemical testing of these materials shows that the fast quenched material has superior capacity and superior retention, being the only variable that shows an increase in capacity during cycling. After 50 full charge / discharge cycles, this material achieves a specific capacity of nearly 230 mAh / g at a C / 2 rate, which is far superior to materials cooled by other methods.
[0117] Rapid, rapid cooling using water immersion during the synthesis of this class of materials results in materials with excellent and distinct crystal structures and previously unreported electrochemical behavior. In particular, we have found that the water-quenched materials (a) exhibit a significant increase in capacity over 50 cycles, (b) do not exhibit the commonly reported voltage fade (where the average discharge voltage of the cell decreases significantly with use), (c) have a specific capacity of greater than 250 mAh / g at C / 2 rate and after 4 cycles at C / 2 rate, and (d) have a specific capacity of greater than 230 mAh / g (e.g., 231-240 mAh / g) after 50 cycles at C / 2 rate, with less than 10% loss in average voltage during discharge.
[0118] FIG. 26A shows the formula Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3)]O2, where the nickel content is x=0.25. z (M y Ni 1-y ) 2-z Also written as O2 (where z=1.16 and y=0.7), it was formed using Hq, Lq and Mq (i.e., water, liquid nitrogen and metal quench, respectively). Figure 26B includes an upper plot showing the trend between lattice parameter "a" and nickel content of the samples, and a lower plot showing the trend between lattice parameter "c" and nickel content of the samples, obtained by single-phase Rietveld fitting.
[0119] As shown in Figure 26A, X-ray diffraction evaluation of the material indicates that the material has a LiNiO2-related hexagonal (e.g., rhombohedral) phase with space group (R-3m) and a Li2NiO3-related monoclinic phase with space group (C2 / c). This suggests that all samples have the predicted layered structure. The diffraction peaks of the monoclinic phase were best defined in the samples produced by the Hq method, suggesting that this method produces a more well-defined crystal structure.
[0120] There was also a superlattice peak near 22° indicative of this family of compounds. The XRD patterns of the 10Lq and 10Mq samples also had significant peaks to the left of the (101), (104), (015), (107), and (108) peaks, suggesting the presence of phase impurities with similar structure and lattice parameters larger than the bulk phase. The absence of other peaks suggests that in this case all impurities are isomorphous with the bulk phase of the material. The XRD pattern of the 10Hq sample showed only small additional (107), (108), and (110) peaks. Although not visible in the XRD patterns, the 17Mq and 25Mq samples also showed the presence of phase impurities with small secondary peaks to the left of the (104) and (107) peaks, respectively. In addition, the (108) peak of the 25Mq sample had a shoulder to its left. Closer examination of the (104) Maxima shows that the differences between the secondary sets of peaks for the 25Hq and 10Mq samples suggest that the isomorphous impurity is probably a nickel-rich layered structure, while the peaks for the 10Lq and 25Mq samples suggest that the isomorphous impurity is probably an ordered rock salt. These data indicate that there are two sources for these sets of peaks, one an additional layered phase and the other an impurity rock salt. As used herein, "secondary layered phase" refers to local regions that have structural variations and correspond to structural distortions, particularly regions with higher nickel content and thus larger lattice parameters, and "impurity" refers to the rock salt phase.
[0121] The lattice parameters of the powders in FIG. 26A were obtained using a Rietveld refinement based on a single phase, with all samples weighted with an R value less than 6, and lattice parameters of known compositions corresponding to bonds found in the literature (see S1, available online at stacks.iop.org / JES / 167 / 160518 / mmedia, incorporated herein by reference in its entirety). The refinement was restricted to a single phase. FIG. 26B shows that the lattice parameter "a" decreases with nickel content in the samples, independent of the quenching method. This same trend is broadly suggested for the lattice parameter "c", although the liquid nitrogen cooled x=0.10, 0.17 and 0.25 samples deviate from this trend. The quenching method at x≧0.10 indicates that a slower quenching method may result in a larger lattice parameter "a", and shows the same general trend for the lattice parameter "c", with the exception of the 10Lq and 17Lq samples.
[0122] In one embodiment, a method of forming an active material for a positive electrode of a lithium ion battery includes quenching the active material in water. In one embodiment, the method further includes calcining the active material powder prior to quenching. The active material may be calcined at a temperature of at least 800° C. The water may be at room temperature prior to quenching, and the active material powder may be quenched at a rate of at least 1750° C. / sec.
[0123] In one embodiment, the active material comprises a layered lithium-rich manganese nickel oxide. Excess Li, Ni, and Mn atoms can be homogeneously and uniformly distributed across the transition metal crystal lattice sites, such that there is no crystal volume exceeding 3×3×3 nm where the difference in the ratios of Ni, Mn, and Li is more than 3% compared to the average ratios of Ni, Mn, and Li atoms in the bulk material. The particles of the active material powder may be in the form of aggregates with an average size in the range of about 0.1 μm to about 20 μm, and the aggregates of the active material powder are composed of microcrystals having an average size in the range of about 25 nm to about 500 nm. The active material powder may contain a composite of hexagonal or monoclinic phases after rapid cooling, and is a combination of the LiMO2 R-3m phase and the Li2MnO3 C2 / m phase (where M is at least one of Ni or Mn). The active material powder may contain a solid solution with a crystal structure having dominant or complete C2 / m symmetry. The active material powder may contain a solid solution with a crystal structure having dominant or complete R-3m symmetry.
[0124] In one embodiment, the active material is represented by the formula Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2 (where 0 < x < 0.5). In one embodiment, the active material is substantially free of cobalt, and the active material is represented by the formula Li[Ni x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2 (where 0.19 < x < 0.26), or by the formula Li[M x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2 (where 0.19 < x < 0.26 and M includes at least one of Ni and Ti, Fe, Al, or Cr).
[0125] In one embodiment, the water contains an additive solvated in the water. The water may contain 0.01 mol / L to 1.0 mol / L of the additive. In one embodiment, the additive includes an acid, which may be selected from sulfuric acid, citric acid, acetic acid, phosphoric acid, hydrochloric acid, ammonium phosphate, or a combination thereof. In another embodiment, the additive includes a carbohydrate, which may be fructose, galactose glucose, lactose, maltose, sucrose, and a combination thereof.
[0126] In one embodiment, the active material is disposed in a positive electrode of a lithium ion battery cell, the lithium ion battery cell further comprising a negative electrode and an electrolyte, the active material comprises hexagonal and monoclinic phases prior to electrochemical cycling of the battery, and the active material powder is free of the monoclinic phase after electrochemical cycling.
[0127] In one embodiment, the specific discharge capacity of the battery cell increases by at least 10% over 50 electrochemical cycles at a charge rate of C / 20 and a discharge rate of C / 2 at room temperature in the voltage range of 2 V to 4.8 V; and the battery cell has a specific capacity of at least 230 mAh / g after 50 electrochemical cycles at a discharge rate of C / 2.
[0128] In one embodiment, a lithium ion battery cell includes a negative electrode; an electrolyte; and a positive electrode including a layered lithium-rich nickel manganese oxide active material, wherein the specific discharge capacity of the battery cell increases by at least 10% over 50 electrochemical cycles at a charge rate of C / 20 and a discharge rate of C / 2, and the battery cell has a specific capacity of at least 230 mAh / g after 50 electrochemical cycles at a discharge rate of C / 2.
[0129] In one embodiment, the specific discharge capacity of the battery cell increases by at least 10% at a charging rate of C / 20 and a discharging rate of C / 20 for two electrochemical cycles in a voltage range of 2V to 4.8V at room temperature, then at a charging rate of C / 20 and a discharging rate of C / 2 for 25 electrochemical cycles, then at a charging rate of C / 20 and a discharging rate of C / 20 for an additional two electrochemical cycles, and then at a charging rate of C / 20 and a discharging rate of C / 2 for 25 electrochemical cycles. In one embodiment, the average discharge voltage of the battery cell does not decrease by more than 10% in 50 electrochemical cycles at a discharging rate of C / 2.
[0130] In one embodiment, the active material is of the formula Li[M x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2 (where 0 < x < 0.5 and M includes Ni or Ni and at least one of Ni, Al, Fe, or Cr). In one embodiment, the active material substantially does not contain cobalt, and the active material is of the formula Li[M x Li (1 / 3-2x / 3) Mn (2 / 3-x / 3) O2 (where 0.19 < x < 0.26 and M includes Ni). In one embodiment, the active material is of the formula y(LiMO2)·(1 - y)LiMnO3 (where y ranges from 0.8 to 1 and M includes at least Ni and Mn).
[0131] In one embodiment, the particles of the active material powder are in the form of aggregates having an average dimension in the range of about 0.1 μm to about 10 μm, the aggregates of the active material powder are composed of microcrystals having an average crystal dimension in the range of about 25 nm to about 500 nm, and the particles of the active material powder have at least one of a spinel surface layer, a carbon coating layer, or an oxygen bond of a passivated surface.
[0132] In one embodiment, the excess Li, Ni and Mn atoms are homogenously and uniformly distributed across the transition metal crystal lattice sites such that no crystalline volume in the material has a Ni, Mn and Li atom ratio that differs by more than 3% compared to the average Ni, Mn and Li atom ratio of the bulk material, the volume being greater than 3×3×3 nm.
[0133] The above description of the disclosed subject matter is provided to enable any person skilled in the art to make or use the present invention. Various modifications to these subject matter will be readily apparent to those skilled in the art, and the generic principles defined herein may be applied to other subject matters without departing from the scope of the present invention. Thus, the present invention is not intended to be limited to the subject matter set forth herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. sintering the lithium-rich metal oxide (LRMO) material at a sintering temperature to form a sintered LRMO material; 4. Rapidly cool the sintered LRMO material from the sintering temperature to room temperature in less than 500 milliseconds to form a molten LRMO material having the chemical formula: Li x (Mn y Ni 1-y ) 2-x O 2 (wherein x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1). forming a quenched LRMO material represented by A method comprising:
2. the sintering temperature is at least 800° C., and The method of claim 1 , wherein said quenching said sintered LRMO material from said sintering temperature to said room temperature comprises quenching said sintered LRMO material from said sintering temperature to said room temperature in 200 milliseconds or less.
3. The sintering temperature is 900° C. to 950° C., and The method of claim 1 , wherein said quenching said sintered LRMO material from said sintering temperature to said room temperature comprises quenching said sintered LRMO material from said sintering temperature to said room temperature in 100 to 200 milliseconds.
4. the sintering comprises sintering the LRMO material in a furnace; and The method of claim 1 , wherein the quenching of the sintered LRMO material comprises quenching the LRMO material in a quench bath.
5. the time from removing the sintered LRMO material from the furnace to quenching the sintered LRMO material in the quench bath to the room temperature of 25° C. is 200 milliseconds or less; and The method of claim 4 , wherein the quench bath comprises a bath containing water.
6. 5. The method of claim 4, wherein the quenching bath comprises an oil bath, an alcohol bath or a water bath containing an additive comprising an acid, a carbohydrate, an alcohol or a combination thereof.
7. forming a mixture of water and organometallic precursors of lithium, nickel and manganese; heating the mixture to form a gel; and pyrolyzing the gel using microwave radiation to form the LRMO material; The method of claim 1 further comprising:
8. the gel comprises an organometallic precursor of 0.01 to 0.20 mole fraction excess of lithium; and The method of claim 7 , wherein the LRMO material comprises an inorganic LRMO material containing lithium, nickel, manganese and oxygen.
9. 10. The method of claim 1, further comprising drying the quenched LRMO material to form a LRMO active material and providing the LRMO active material in a cathode electrode of a lithium ion battery containing an anode electrode and an electrolyte.
10. The LRMO active material is selected from the group consisting of: the crystalline particles of the LRMO active material exhibit a uniform distribution of Mn and Ni atoms throughout the crystalline particles such that there are no regions that are Ni-rich or Mn-rich when imaged by HAADF EDS; an increase of at least 6% in the ratio of the (006)+(102):(101) x-ray diffraction peaks when compared to an unquenched LRMO material having the same composition; a ratio of the (003) to (104) X-ray diffraction peaks greater than 2; providing a specific capacity of at least 165 mAh / g upon first discharge of said lithium ion battery; less than 10% loss in average discharge voltage after 200 charge / discharge cycles at a C / 20 rate of said lithium ion battery; or Less than 10% capacity fade over more than 200 C / 5 charge / discharge cycles of said lithium ion battery The method of claim 9 , further comprising at least one of:
11. pyrolyzing the precursor material using microwave radiation to form a pyrolyzed lithium-rich metal oxide (LRMO) material; sintering the pyrolyzed LRMO material to form a sintered LRMO material; 4. Quenching the sintered LRMO material to form a molten SiO2 having the chemical formula: Li x (Mn y Ni 1-y ) 2-x O 2 (wherein x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1). forming a quenched LRMO material represented by A method comprising:
12. 12. The method of claim 11, wherein the precursor material comprises an organometallic precursor of Li, Mn and Ni selected from at least one of acetates, carbonates, nitrates, sulfates or hydroxides of Li, Mn and Ni.
13. forming a mixture of water and said organometallic precursors of lithium, nickel and manganese; heating the mixture to form a gel; and wherein said step of pyrolyzing said precursor material comprises heating said gel with microwave radiation, said gel comprising an organometallic precursor of 0.01 to 0.20 mole fraction excess of lithium.
14. 12. The method of claim 11, wherein the precursor material comprises a precursor that is a co-precipitated hydroxide of Mn and Ni mixed with lithium carbonate.
15. The method of claim 11 , wherein the quenching comprises quenching the sintered LRMO material from the sintering temperature to room temperature in less than 500 milliseconds to form a quenched LRMO material.
16. 12. The method of claim 11, further comprising drying the quenched LRMO material to form a LRMO active material and providing the LRMO active material to a cathode electrode of a lithium ion battery containing an anode electrode and an electrolyte.
17. A cathode electrode active material having the chemical formula: Li x (Mn y Ni 1-y ) 2-x O 2 (wherein x is greater than 1.05 and less than 1.25, and y is in the range of 0.95 to 0.1). It is expressed as the active material comprises a layered hexagonal phase and a monoclinic phase, and The active material is selected from the group consisting of: a (006)+(102):(101) X-ray diffraction peak intensity ratio of greater than 0.32; when included in a lithium ion battery, providing a specific capacity of at least 165 mAh / g at first discharge at a C / 20 rate; When included in a lithium ion battery, less than a 10% loss in average discharge voltage after 100 charge / discharge cycles at a C / 20 rate; or Less than 10% capacity fade over 100 C / 5 charge / discharge cycles when included in a lithium-ion battery The active material exhibits at least one of the following:
18. The method of claim 17 , wherein the particles of active material include a carbon coating or an acid-modified surface.
19. 18. The active material of claim 17, wherein the active material exhibits a (006)+(102):(101) x-ray diffraction peak intensity ratio of greater than 0.
32.
20. 20. The active material of claim 19, wherein the active material exhibits a ratio of the (003) to (104) x-ray diffraction peaks greater than 2.
21. 18. The active material of claim 17, wherein the crystalline particles of the active material exhibit a uniform distribution of Mn and Ni atoms throughout the crystalline particles such that there are no regions that are Ni-rich or Mn-rich when imaged by HAADF EDS.
22. A cathode electrode comprising the active material of claim 17; an anode electrode; Electrolytes and Including, lithium ion battery.
23. 23. The battery of claim 22, wherein the active material provides a specific capacity of at least 165 mAh / g at a first discharge of the lithium ion battery at a C / 20 rate.
24. 23. The battery of claim 22, wherein the lithium ion battery has less than a 10% loss in average discharge voltage after 100 charge / discharge cycles at a C / 20 rate.
25. 23. The battery of claim 22, wherein the active material exhibits less than 10% capacity fade over 100 C / 5 charge / discharge cycles.
26. The average discharge voltage of the lithium ion battery does not decrease by more than 5% over 50 C / 20 (charge) - C / 2 (discharge) charge / discharge cycles; or 23. The battery of claim 22, wherein the discharge capacity of the lithium ion battery is greater than 80% of its original capacity after 800 or more C / 20-C / 2 charge / discharge cycles.
27. 23. A method of operating a lithium ion battery as claimed in claim 22, comprising performing a plurality of charge / discharge cycles, the active material provides the 165 mAh / g specific capacity upon first discharge of the lithium ion battery at a C / 20 rate; the lithium ion battery having a loss in average discharge voltage of less than 10% after 100 charge / discharge cycles at a C / 20 rate; The method, wherein the active material exhibits less than 10% capacity fade over more than 100 C / 5 charge / discharge cycles.